Biofilm formation by Staphylococcus aureus isolates from a dental clinic in Konya, Turkey - Emrah Torlak; Emre Korkut; Ali T. Uncu; Yağmur Şener (Elsevier, 2017)
The ability of Staphylococcus aureus to form biofilm is considered to be a major virulence factor influencing its survival and persistence in both the environment and the host. Biofilm formation in S. aureus is most frequently associated with production of polysaccharide intercellular adhesion by ica operon-encoded enzymes. The present work aimed at evaluating the in vitro biofilm production and presence of the icaA and icaD genes in S. aureus isolates from a dental clinic in Konya, Turkey. The surfaces of inanimate objects were sampled over a period of six months. S. aureus isolates were subjected to Congo Red Agar (CRA) and crystal violet (CV) staining assays to evaluate their ability of biofilm production, while the presence of the icaA and icaD genes was determined by polymerase chain reaction. S. aureus contamination was detected in 13.2% of the environmental samples. All the 32 isolates were observed to be positive for both the icaA and icaD genes. Phenotypic evaluations revealed that CV staining assay is a more reliable alternative to CRA assay to determine biofilm formation ability. A high percentage of agreement (91%) was observed between the results from CV staining and ica genes' detection assays. Phenotypic and genotypic evaluations should be combined to detect biofilm formation in S. aureus. Our findings indicate that dental clinic environments should be considered as potential reservoir for biofilm-producing S. aureus and thus cross contamination. Keywords: Staphyloccocus aureus, Dental clinic surfaces, Biofilm, ica genes, Konya